Genetic effects on carcass traits in F1 cockerels from reciprocal crosses of Fayoumi and two exotic chicken breeds - Fikrineh Negash; Ashenafi Getachew (Journal of Agriculture and Food Research)
This study examined the genetic basis of carcass traits in F1 cockerels produced through reciprocal crosses between the tropically adapted Fayoumi (FM) breed and two exotic breeds: dual-purpose Koekoek (KK) and layer-type White Leghorn (WL). Utilizing a diallel model, we evaluated both additive (purebred effects [PE], general combining ability [GCA], maternal effects [ME]) and non-additive (specific combining ability [SCA], residual reciprocal effects [RRE], and heterosis) genetic components for live weight, dressed carcass weight, and yields of carcass parts and edible offal in purebred and crossbred genotypes. The analysis revealed significant genetic variation (p < 0.05) among genotypes, with KK♂ × FM♀ crosses and purebred KK demonstrating superior performance for most traits. The KK♂ × FM♀ crosses achieved the highest live weight (1720.50 g) and dressed carcass weight (1371.33 g), significantly outperforming other genotypes. Additive genetic effects were particularly pronounced, with KK showing strong positive PE and GCA values (p < 0.05), while FM and WL exhibited favorable ME. Non-additive genetic effects were equally important, with heterosis reaching 16–23 % for critical traits in optimal crosses. The KK♂ × FM♀ crosses showed the highest heterosis values, while FM♂ × WL♀ displayed superior SCA effects for all traits, suggesting additional potential for genetic improvement through targeted crossbreeding strategies. These findings demonstrate that KK serves as an optimal sire line due to its strong additive genetic contributions, while FM and WL function effectively as dam lines through their maternal genetic effects. The results underscore the value of strategic crossbreeding programs that capitalize on both additive and non-additive genetic variation to enhance poultry productivity in tropical smallholder farming systems, particularly in Ethiopia and similar agroecological contexts.